Relationship between immune checkpoint proteins, tumour microenvironment characteristics, and prognosis in primary operable colorectal cancer - Sara SF Al‐Badran; Lauren Grant; Maejoy V Campo; Jitwadee Inthagard; Kathryn Pennel; Jean Quinn; Prakash Konanahalli; Liam Hayman; Paul G Horgan; Donald C McMillan; Campbell SD Roxburgh; Antonia Roseweir; et al. (Wiley, 2021)
Abstract The tumour microenvironment is an important factor for colorectal cancer prognosis, affecting the patient's immune response. Immune checkpoints, which regulate the immune functions of lymphocytes, may provide prognostic power. This study aimed to investigate the prognostic value of the immune checkpoints TIM‐3, LAG‐3 and PD‐1 in patients with stage I-III colorectal cancer. Immunohistochemistry was employed to detect TIM‐3, LAG‐3, PD‐1 and PD‐L1 in 773 patients with stage I-III colorectal cancer. Immune checkpoint protein expression was assessed in tumour cells using the weighted histoscore, and in immune cells within the stroma using point counting. Scores were analysed for associations with survival and clinical factors. High tumoural LAG‐3 (hazard ratio [HR] 1.45 95% confidence interval [CI] 1.00-2.09, p = 0.049) and PD‐1 (HR 1.34 95% CI 1.00-1.78, p = 0.047) associated with poor survival, whereas high TIM‐3 (HR 0.60 95% CI 0.42-0.84, p = 0.003), LAG‐3 (HR 0.58 95% CI 0.40-0.87, p = 0.006) and PD‐1 (HR 0.65 95% CI 0.49-0.86, p = 0.002) on immune cells within the stroma associated with improved survival, while PD‐L1 in the tumour (p = 0.487) or the immune cells within the stroma (p = 0.298) was not associated with survival. Furthermore, immune cell LAG‐3 was independently associated with survival (p = 0.017). Checkpoint expression scores on stromal immune cells were combined into a Combined Immune Checkpoint Stromal Score (CICSS), where CICSS 3 denoted all high, CICSS 2 denoted any two high, and CICSS 1 denoted other combinations. CICSS 3 was associated with improved patient survival (HR 0.57 95% CI 0.42-0.78, p = 0.001). The results suggest that individual and combined high expression of TIM‐3, LAG‐3, and PD‐1 on stromal immune cells are associated with better colorectal cancer prognosis, suggesting there is added value to investigating multiple immune checkpoints simultaneously.